2016
DOI: 10.3390/mi7010007
|View full text |Cite
|
Sign up to set email alerts
|

Study on Improving Thickness Uniformity of Microfluidic Chip Mold in the Electroforming Process

Abstract: Electroformed microfluidic chip mold faces the problem of uneven thickness, which decreases the dimensional accuracy of the mold, and increases the production cost. To fabricate a mold with uniform thickness, two methods are investigated. Firstly, experiments are carried out to study how the ultrasonic agitation affects the thickness uniformity of the mold. It is found that the thickness uniformity is maximally improved by about 30% after 2 h electroforming under 200 kHz and 500 W ultrasonic agitation. Secondl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The researches [13,24] have shown that the width of auxiliary cathode and the distance between auxiliary cathode and the microstructure have direct effect on thickness uniformity of the electroformed microstructure. In order to quickly determine the dimensions and placement of auxiliary cathode, the computer-aided analysis is performed to simulate electroforming process.…”
Section: Simulation Study Of the Auxiliary Cathodementioning
confidence: 99%
See 2 more Smart Citations
“…The researches [13,24] have shown that the width of auxiliary cathode and the distance between auxiliary cathode and the microstructure have direct effect on thickness uniformity of the electroformed microstructure. In order to quickly determine the dimensions and placement of auxiliary cathode, the computer-aided analysis is performed to simulate electroforming process.…”
Section: Simulation Study Of the Auxiliary Cathodementioning
confidence: 99%
“…But for longtime electroforming, the high temperature and pressure caused by ultrasonic cavitation may destroy the photoresist structures [21], which limits the application of ultrasonic electroforming to a certain extent. Because electric field distribution directly determines the thickness uniformity of micro electroforming, the methods of optimizing electric field distribution, such as auxiliary cathode [13,[22][23][24] and insulating shield [25] have been developed. The auxiliary cathode method is a more effective way to decrease the edge effect of current in micro electroforming than insulating shield method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, there is an increasing demand for micro structures of micron-scale line widths and high aspect ratios due to the rising functionality of micro-devices. With the advantages of precision features, ultra-smooth surface finish and mass production capability, the LIGA technique has emerged as the suitable method for large-scale fabrication of micro-devices, such as microfluidic chips, [1][2][3] micro-molds, 4,5 and optical systems. 6,7 As one of the major steps in LIGA, micro-electroforming has the ability to accurately replicate patterned micro molds through the deposition of metal atoms and consequently plays an increasingly important role in the manufacture of mold inserts.…”
Section: Introductionmentioning
confidence: 99%
“…This process demonstrates high precision but requires expensive masters and takes several weeks to complete the entire process. The thickness uniformity and flatness can be constrained when growing thick deposits [2].…”
Section: Introductionmentioning
confidence: 99%